The role of research & development as mediating the effect of male CEO masculinity face on earnings management: evidence from Indonesia - Indra Prasetyo; Nabilah Aliyyah; Esa Wahyu Endarti; Rusdiyanto Rusdiyanto; Aulia Rahmawati (Cogent Business & Management, 2022)
This study aims to prove the consistency of Agency Theory, Behavioral Consistency Theory and Upper Echelon Theory as a solution to explain the role of research & development in mediating the influence of male CEO masculinity on earnings management. This study uses a quantitative approach with a population and research sample using companies on the Indonesia Stock Exchange in 2016-2021. The study collected images of faces identified as male CEOs from data from the Indonesia Stock Exchange website and company websites and using a Google search. The data analysis method in this study uses Structural Equation Modeling (SEM) with Stata Software which connects theories, concepts and data that can be carried out on research variables. The findings explain that the decrease and increase in research and development practices have an impact on increasing and decreasing the value of CEO masculinity men also have an impact on the increase and decrease in the value of research & development companies. The empirical findings have implications for the consistency of Agency Theory, Behavioral Consistency Theory and Upper Echelon Theory. While the findings have practical implications, the findings as policy makers are related to the face of male CEO masculinity as a determinant of earnings management practices and research & development costs.
Keywords: G32; G34; G02; M1; Z1; 650; R&D; earnings management; CEO male; masculinity; Stata